2010
DOI: 10.1007/s11101-010-9164-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental biotic factors on the content of saponins in plants

Abstract: Saponins occur constitutively in many plant species as part of their defense system. However, saponin content in plants seems to be dynamic, responding to many external factors including various biotic stimuli connected to herbivory attack and pathogenic infection, as well as involved in plant mutualistic symbioses with rhizobial bacteria and mycorrhizal fungi. Thus, not only saponins influence the living organisms interacting with plants, but in turn, all these interactions can impact the plant saponin conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 47 publications
0
53
0
3
Order By: Relevance
“…Observed variation in saponin content of various green leafy vegetables studied, showed that different vegetables have ability to produce these secondary metabolites as a result of genetic constitution of the plants and or other environmental factors [17,18]. High saponin levels were observed in Telferia ocidentalis, Colocacia argente, Lunea taraxacifolia and Ammmarantus viridis, having saponin in mg/100g dry weight, well above 400.…”
Section: Discussionmentioning
confidence: 96%
“…Observed variation in saponin content of various green leafy vegetables studied, showed that different vegetables have ability to produce these secondary metabolites as a result of genetic constitution of the plants and or other environmental factors [17,18]. High saponin levels were observed in Telferia ocidentalis, Colocacia argente, Lunea taraxacifolia and Ammmarantus viridis, having saponin in mg/100g dry weight, well above 400.…”
Section: Discussionmentioning
confidence: 96%
“…Mineral soil conditions for N, P and K varied among the evaluated sectors, but K content was higher at Quebrada Honda than at Gualliguaica and Manquehua. The presence of the components in the fruits is highly regulated by both genetic and environmental (soil and climate), factors (Lester and Crosby, 2002;Lester, 2006;Guzmán-Maldonado et al, 2010;Szakiel et al, 2010).…”
Section: Fruit Fractionmentioning
confidence: 99%
“…The number and quantitative variation of plant secondary metabolites are affected by their around growing environment, which including biotic and abiotic factors (Szakiel et al, 2011a;2011b). The biotic factors contain interactions between plants and their enemies or allies (Szakiel et al, 2011a); and the abiotic factors include temperature, soil fertility, water and light (Szakiel et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The number and quantitative variation of plant secondary metabolites are affected by their around growing environment, which including biotic and abiotic factors (Szakiel et al, 2011a;2011b). The biotic factors contain interactions between plants and their enemies or allies (Szakiel et al, 2011a); and the abiotic factors include temperature, soil fertility, water and light (Szakiel et al, 2011b). The assumptions tested by a number of studies are being approved, reveal that secondary metabolites especially phenolic compounds are stimulated to synthesize under adverse conditions but restrained under good conditions for growth (Liu et al, 2010a;Liu et al, 2010b;Ibrahim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%